Phylogenetic relationships of Icacinaceae focusing on the vining genera. (November 2014) - Byng, James W.; Bernardini, Benedetta; Joseph, Jeffrey A.; Chase, Mark W.; Utteridge, Timothy M. A.
<x xml:space="preserve">Abstract</x> Phylogenetic relationships of the pantropical and polyphyletic family Icacinaceae were investigated, focusing on the Old World vining genera. Plastid ndhF, rbcL and matK sequences from taxa representing 32 of the 36 currently recognized genera were analysed with maximum parsimony and Bayesian methods. As in previous studies, our results show that the family is divided into several poorly resolved groups. An evaluation of the traditional tribal classification revealed Iodeae as polyphyletic and the monogeneric Sarcostigmateae as sister to a monophyletic Phytocreneae (with the inclusion of Rhyticaryum). In Iodeae, the monospecific, eastern Malesian Polyporandra was embedded in the Old World Iodes. A strongly supported clade containing Phytocreneae plus Rhyticaryum was present in the Icacina group. The tropical African genera Chlamydocarya and Polycephalium were embedded in the Old World Pyrenacantha. Further relationships in the family and potential synapomorphic characters of the clades are discussed. New combinations are made for Polyporandra and Chlamydocarya/Polycephalium spp., which are formally synonymized with Iodes and Pyrenacantha, respectively. Conclusions about family‐level relationships (and circumscription) cannot be reached with these data because of several weakly supported inter‐relationships between some clades, such as Cassinopsis, Platea/Calatola and the Emmotum group. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 176, 277–294.